Resurrection of the dead in early Judaism, 200 BCE-CE 200 - Elledge, Casey D. (Oxford University Press USA - OSO, 2017)
A study of the formation and development in early Judaism of a belief in a future resurrection from the grave. It draws on evidence from the Apocrypha, Pseudepigrapha, the Dead Sea Scrolls, inscriptions, and archaeology.